Competitive Allele Specific Polymerase chain reaction markers identified for important contributor to dietary fibre in wheat - CGIAR Research Program on Wheat (2021)
A predicted gene encoding for a glycosyl transferase (GT) of the GT61 family was identified. This information is now ready to use for wheat breeders.